USED LUBRICANT OIL PURIFICATION WITH ACID AND CLAY METHOD - Asih Wijayanti (President University, 2023)
The power generation industry from every production process certainly produces non-toxic and hazardous waste and toxic and hazardous waste. One of the toxic and hazardous waste of used lubricating oil. This scientific work aims to analyze the characteristics of used lubricating oil to be used as raw material for purification and to determine the most optimal quality of the purified lubricating oil from the addition of acid and bentonite clay. The research method starts from a preliminary test by knowing the characteristics of used lubricating oil, followed by activation bentonite clay with hydrochloric acid, preparation of used lubricating oil with hydrochloric acid, adsorption process with the addition of hydrochloric acid and bentonite clay as adsorbent and the mass variation is 10 gr, 15 gr, and 20 gr with the temperature variation is 85°C, 95°C, and 105°C in order to obtain 9 variations. After the purification process is carried out, the characteristics of the lubricating oil are obtained with optimum conditions of 9 variations, namely 20 gr bentonite clay and the temperature is 105°C (B20T105) so the conclusion are obtained based on the results of the purification analysis, namely the parameters of water content, specific gravity, and total acid number still meet the standards for the use of lubricating oil. As for the kinematic viscosity, it still does not meet the standards for the use of lubricating oil.